The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ol0492391
|View full text |Cite
|
Sign up to set email alerts
|

Allenes and Transition Metals:  A Diverging Approach to Heterocycles

Abstract: [reaction: see text] An alkynyl allene has been converted to heterocycles possessing an alpha-alkylidene cyclopentenone, a 4-alkylidene cyclopentenone, or a cross-conjugated triene. Thus, a common intermediate has been converted to three structurally unique compounds by changing only the reaction conditions and, therefore, controlling various reaction pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 7 publications
1
57
0
2
Order By: Relevance
“…1). For example, reaction of allene-yne 1 with molybdenum hexacarbonyl [MoðCOÞ 6 ] affords alkylidene cyclopentenone 2 by a selective reaction with the proximal double bond of the allene (8). Alternatively, reaction of the allene-yne 1 with 5 mol% of rhodium biscarbonyl chloride dimer ½RhðCOÞ 2 Cl 2 under a carbon monoxide atmosphere gives the 4-alkylidene cyclopentenone 3 via a selective cyclocarbonylation reaction with the distal double bond of the allene.…”
Section: Resultsmentioning
confidence: 99%
“…1). For example, reaction of allene-yne 1 with molybdenum hexacarbonyl [MoðCOÞ 6 ] affords alkylidene cyclopentenone 2 by a selective reaction with the proximal double bond of the allene (8). Alternatively, reaction of the allene-yne 1 with 5 mol% of rhodium biscarbonyl chloride dimer ½RhðCOÞ 2 Cl 2 under a carbon monoxide atmosphere gives the 4-alkylidene cyclopentenone 3 via a selective cyclocarbonylation reaction with the distal double bond of the allene.…”
Section: Resultsmentioning
confidence: 99%
“…38 Nielsen e Schreiber identificaram uma estratégia comum a muitos dos processos de síntese orientada pela diversidade estrutural, a qual eles chamaram de construir/acoplar/parear. 40,41 Nos últimos anos alguns trabalhos têm sido desenvolvidos combinando o conceito de síntese orientada pela diversidade estrutural com o conceito de estruturas privilegiadas. Esta estratégia se baseia no fato de que algumas classes de esqueletos moleculares (estruturas privilegiadas) são capazes de atuar como ligantes para diversos receptores biológicos, devido às suas propriedades físico-químicas favoráveis.…”
Section: Esquema 5 Estratégia Para a Geração Dos Compostos Macrocíclunclassified
“…Our group previously demonstrated that various reaction topologies could be controlled by a proper choice of the transition metal catalyst, as well as the functionalization of the starting enyne (7-10). Significant advances in this area can now enable incorporation of such transformations into synthetic strategies for the assembly of skeletally diverse chemical libraries (11)(12)(13)(14)(15)(16)(17)(18). However, several challenges remain to be addressed to facilitate access to high-diversity chemical libraries.…”
mentioning
confidence: 99%